Analysis of Da’if & Mawdu’ Hadith in the Book of Ta’lim Al-Muta’allim by Shaykh Al-Zarnuji - Kirin, Arwansyah; Wan Zahari, Wan Ainaa Mardhiah; Husen Ismail, Faisal; Marpuah, Siti; Ahmade, Norhafizah; Borham, Abdul Shakor (2021)
Ta’lim al-Muta’allim’s book by Sheikh al-Zarnuji is a turath book containing ethics and manners of learning and teaching between teachers and students. This book is famous and distributed in the Archipelago especially in Malaysia and Indonesia. It is also widely used in pesantran or pondok nowaday. Sheikh al-Zarnuji used hadiths of prophet Muhammad s.a.w as the main source and hujjah in Ta’lim al-Muta’allim’s book. He also included some other categories of hadith including da’if and mawdu’ hadiths. The issue is Ta’lim al-Muta’llim’s book contains many da’if and mawdu’ hadiths and have been referred by Muslim. This study is very important to understand the method and rule of practicing of da’if and mawdu’ hadiths. Hence, this study aimed to analyse da’if and mawdu’ hadiths contained in Ta’lim al-Muta’llim’s book. The methodology of this hadith is qualitative method by using content analysis approach toward Ta’lim al-Muta’llim’s book. Thus, the finding for the analysis of 40 hadiths in this book found that only 30% hadith can be used for fada’il al-amal if fulfilled the conditions by the ulama’s. Hence, thematic analysis is important to be done in order to ensure the quantity of da’if and mawdu’ hadiths in this book and also to ensure the da’if hadith can be practiced only for fada’il al-amal matter.